Same-Race Student–Teacher: Comparing Outcomes for Kindergartners With and Without Disabilities. (August 2019) - Gottfried, Michael A.; Kirksey, J. Jacob; Wright, Adam
Although numerous studies have examined if students of color benefit from having a teacher of the same race/ethnicity, all attention has been paid to students without disabilities. We examine whether the same benefits hold for students with disabilities (SWDs). Using a nationally representative data set of kindergartners, we explored whether SWDs of color had different academic and social–emotional outcomes when with a teacher of the same race/ethnicity. We compared students of color with and without disabilities in the same classroom with regard to a same-race teacher match. Unlike students without disabilities, we do not find evidence in the data set that SWDs of color benefit from a same-race teacher match in terms of achievement and social–emotional development. Implications with regard to educational equity are discussed.